The Semantic Web Fourth Asian Conference, ASWC 2009, Shanghai, China, December 6-9, 2008. Proceedings - Yu, Yong-jiang; Ding, Ying (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the refereed proceedings of the fourth Asian Semantic Web Conference, ASWC 2009, held in Shanghai, China, in December 2009. The 35 revised full papers presented were carefully reviewed and selected from 63 submissions. These submissions cover a broad range of topics including, query languages and optimization, rule and logics, scalable reasoning, semantic content generation, database and semantics, semantic web services, eSemantics (e.g., e-Business, e-Science, e-Learning, e-Culture, e-Health), social web and semantics, semantic graph mining, security for semantic web, ontology modeling, ontology management, to name a few.